Design of a clutchless automated gear control system for electric tractors - Bingöl, Bertuğ (Graduate School, 2025)
The electrification of agricultural machinery is becoming increasingly important due to rising fossil fuel prices and stringent environmental regulations aimed at reducing emissions. In developing countries, agricultural activities account for approximately 35% of total emissions, making the transition in this sector inevitable. Compared to internal combustion engines, electric agricultural machinery offers significant advantages in terms of higher energy efficiency, lower operational costs, and improved sustainability. Moreover, electrification not only enhances energy efficiency but also enables various subsystems within the vehicle architecture to become more effective and reliable. During this transformation process, traditional mechanical components are being replaced by advanced electronic and software-based control strategies. This study focuses on the control of a dog clutch mechanism that enables automated and clutchless gear shifting, with the objective of developing a more efficient and reliable gear transition method. While conventional synchronization methods rely on mechanical components, software-based control strategies allow for more precise synchronization of motor speeds, leading to smoother and more efficient gear transitions. The study utilizes optimized gear ratios and implements gear shifting through hydraulic actuators, which have been relatively less explored in the literature. While most existing studies focus on using electric motors for gear synchronization, this research prioritizes hydraulic actuators, leveraging the vehicle's existing hydraulic system. This approach not only makes efficient use of the available hydraulic infrastructure but also highlights the advantages of hydraulic systems over electrical ones, particularly in terms of instantaneous power transfer and high-power capacity. The primary objective of this research is to develop an optimized gear control algorithm for agricultural machinery, enabling the electronic control of a dog clutch mechanism in a moving vehicle. To achieve this, real-time feedback mechanisms have been developed through the vehicle management unit to enhance gear shift accuracy and improve system response time. Two different software algorithms—one incorporating active speed synchronization and the other without it—were tested on an actual vehicle to evaluate their performance and compare their benefits. The developed software aims to reduce reliance on mechanical components, thereby enhancing system durability and long-term operational stability. This thesis contributes to the advancement of software-based gear control in electric agricultural machinery, aiming to eliminate the inefficiencies of traditional systems. The performance of the developed algorithms has been evaluated under field conditions, demonstrating their advantages over conventional systems. Ultimately, the proposed approach seeks to reduce the number of gears in equivalent internal combustion engine-powered agricultural vehicles from up to 32 to just 2, thereby minimizing maintenance requirements, reducing system complexity, and optimizing dimensional efficiency.
Elektrikli traktörler için debriyajsız otomatize vites kontrol sistemi tasarımı
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2025
Keywords: electric tractors; elektrikli traktör